The interactive effects of dual‐earner couples' job insecurity: Linking conservation of resources theory with crossover research. Issue 2 (2nd February 2017) - Debus, Maike E.; Unger, Dana
Abstract : The present study examines job insecurity in the context of dual‐earner couples. Linking conservation of resources theory (e.g., Hobfoll, 1989, Am. Psychol., 44, 513) with crossover research (e.g., Westman, 2001, Hum. Relat., 54, 717), we proposed that a partner's job insecurity constitutes an additional resource threat. Thus, the partner's job insecurity would exacerbate a person's negative reaction to his or her own job insecurity in terms of attitudinal (i.e., work engagement) and both health‐ and withdrawal‐related outcomes (i.e., psychological health and turnover intention). Using a time‐lagged design and multisource data from 171 mixed‐gender dual‐earner couples, multilevel path analysis applying the Actor‐Partner‐Interdependence Model revealed interesting gender differences. The negative relationship between the husband's job insecurity and his work engagement was stronger, the higher his wife's job insecurity was. The data further showed a moderated mediation, such that the husband's job insecurity was negatively and indirectly related to both psychological health and turnover intention (via reduced work engagement) if his wife experienced a medium or high level of job insecurity. Our study demonstrates the interactive effects of stressors in dual‐earner couples, and highlights the importance of overcoming an overly individualistic perspective when studying job insecurity in particular and stressors more generally. Practitioner points: Job insecurity has become a highly potent stressor for a large number of employees nowadays. In the context of dual‐earner couples, we demonstrate that husbands react more negatively to job insecurity if their wives experience job insecurity too. Dual‐earner couples are advised to diversify their occupational background, such that economic downturns in one industry sector are less likely to hit both partners. Due to the fact that particularly husbands were affected by the job insecurity of their wives, it is important to tailor psychotherapeutic approaches to this group. Because men are usually more reluctant to approach psychotherapeutic counselling, the rise of job insecurity underscores the need to circumvent chronic mental health problems with adequate interventions. Companies are advised to communicate with their employees in a transparent way, such that employees can better cope with organizational plans relating to mergers, acquisitions, and downsizing.